Nanocellulose from oil palm mesocarp ﬁber using hydrothermal treatment with low concentration of oxalic acid - Noor Fitrah, Abu Bakar; Norazah, Abd A. Rahman; Mahazmi Burhanudin, Mahadi; Syaidatul Akma, Mohd Zuki; Khairatun Najwa, Mohd Amin; M. Z., Wahab; Lenggoro, Wuled (Elsevier Ltd, 2021)
Nanocellulose from oil palm mesocarp fiber (OPMF) was isolated using hydrothermal treatment at a pressure of 150 kPa and 120 C coupled with hydrolysis of low concentration of weak acid i.e. oxalic acid dihydrate (OAD). Two different concentrations of OAD i.e. 11 and 13 wt% were introduced in the acid hydrolysis process. Crystallinity index of the raw fiber increased from 39.5 to 70.4 and 70% for 11 and 13 wt% OAD, respectively. The average particles sizes of nanocellulose measured using TEM was approximately 25 nm for both concentrations of OAD which approximately equivalent to the one measured using dynamic light scattering (DLS). The values of zeta potential of the nanocellulose suspension isolated using 11 and 13 wt% OAD were _26 and _27.5 mV respectively. Isolation technique which is hydrothermal treatment coupled with low concentration of OAD was effective in producing OPMF nanocellulose at high crystallinity index, less than 100 nm size distribution, and it is a stable suspension.